Global sourcing in integrated network structures: The case of hybrid purchasing organizations - Trautmann, Gerhard; Bals, Lydia; Hartmann, Evi (Journal of International Management, 2009)
An issue for companies in globally competitive markets is to adapt their organizational structures and governance in increasingly complex organizations. At the functional level of purchasing, companies are turning to hybrid purchasing organizations in order to leverage global sourcing benefits. One of the key challenges in this context is to distinguish between categories to be integrated across sites and those that are to remain under the authority of each purchasing location in order to maximize purchasing synergies. This paper presents a purchasing portfolio model that provides a comprehensive view of relevant global synergy dimensions. Based on a literature review, a theoretically-grounded purchasing portfolio model for global sourcing is developed. The theoretical basis stems from information processing theory, organizational buying behavior (OBB) and transaction cost economics. The validity of the model is explored by means of case study research. Complementing the extant literature, the theoretical contribution of the paper lies in not only addressing category selection criteria for exploiting economies of scale, but also for economies of information and learning and economies of process. Furthermore, it provides insights regarding integrated network coordination mechanisms at the functional level of purchasing.
WiSo-Import:2015-03-26:1018
Keywords: Purchasing; Portfolio model; Multinational corporations; MNCs; Integrated network structure; Hybrid organization; Global sourcing; Case study; Innovation